The Publication Rates of Pediatric Rheumatology Abstracts Presented in European League Against Rheumatism 2009 Congress - Özge Altuğ GÜCENMEZ; Deniz BAYRAKTAR; Umut Ziya KOÇAK; Balahan MAKAY; Şevket Erbil ÜNSAL (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate the publication rates and features of the abstracts related to pediatric rheumatology presented in European League against Rheumatism 2009 congress. Methods: A systematic search was performed to find full-text publications of abstracts related to pediatric rheumatology in European League against Rheumatism 2009 congress. Full-text publication rate, the elapsed time between presentation and full-text publication, type of the disease in the studies, distribution of abstracts and full-texts according to countries, journals, and presentation types were investigated. Results: Totally 220 abstracts were detected related to pediatric rheumatology. Twenty-two of them had only the title, authors’ names, and institution of origin, but no abstract. Therefore, a total number of 198 abstracts were evaluated. Eighty-six (43.4%) abstracts were found to be accepted as full-text articles. The elapsed time between presentation and full text publication was median 19 months (range 0 to 64 months). While 12 orally presented abstracts (34%) became full-text articles, this rate was 45% (74 abstracts) for poster presentations. There was no significant difference in the elapsed time to reach full-text publication and impact factors between presentation types (p=0.832 and p=0.053, respectively). Conclusion: The full-text publication rates were within similar ranges when compared to other reports in rheumatology field. It seems that even though European League against Rheumatism is a general rheumatology congress, it takes an important place in pediatric rheumatology field as well.